2016
DOI: 10.3390/beverages2030019
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumer Preferences for Australian Sparkling Wine vs. French Champagne

Abstract: Sparkling wine represents a small but significant proportion of the Australian wine industry's total production. Yet, Australia remains a significant importer of French Champagne. This study investigated consumer preferences for Australian sparkling wine vs. French Champagne and any compositional and/or sensorial bases for these preferences. A range of French and Australian sparkling wines were analyzed by MIR spectroscopy to determine if sparkling wines could be differentiated according to country of origin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
4
21
0
1
Order By: Relevance
“…One hundred and forty consumers were recruited to participate in acceptance tests (Table ), with a considerably higher proportion of women being recruited than men (68 vs 32%). This was not entirely surprising given the perception that sparkling wine is a ‘female drink’ (Charters et al ) and the self‐selecting nature of recruitment and was consistent with the gender bias (in favour of female participants) experienced in several other recent sparkling wine‐related studies involving consumer trials (Culbert et al , , Verdonk et al ). A higher proportion of younger consumers (aged 18 to 34 years) was also recruited, being 40% compared with 31.4 and 25.7%, for 35‐ to 54‐year‐olds and ≥55‐year‐olds, respectively.…”
Section: Resultssupporting
confidence: 75%
“…One hundred and forty consumers were recruited to participate in acceptance tests (Table ), with a considerably higher proportion of women being recruited than men (68 vs 32%). This was not entirely surprising given the perception that sparkling wine is a ‘female drink’ (Charters et al ) and the self‐selecting nature of recruitment and was consistent with the gender bias (in favour of female participants) experienced in several other recent sparkling wine‐related studies involving consumer trials (Culbert et al , , Verdonk et al ). A higher proportion of younger consumers (aged 18 to 34 years) was also recruited, being 40% compared with 31.4 and 25.7%, for 35‐ to 54‐year‐olds and ≥55‐year‐olds, respectively.…”
Section: Resultssupporting
confidence: 75%
“…Similarly, consumers who indicated they consumed sparkling wine regularly, at least once a fortnight, tended to like sparkling wines more than other consumers. Previous research has shown that consumer preferences for wine, including sparkling wine and Champagne, can vary considerably (Lange et al , Combris et al , Vignes and Gergaud , Culbert et al ), so cluster analysis was employed to differentiate consumers based on their individual liking scores. Four distinct clusters comprising consumers with different preferences for the subset of sparkling wines were identified (Tables and ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have focussed on the physical attributes of sparkling wine, such as foam quality (Brissonet and Maujean , Andrés‐Lacueva et al , , Vanrell et al ), effervescence (Liger‐Belair ) and bubble nucleation (Liger‐Belair et al ), or measurement of foaming properties (Condé et al ). Whilst a recent study evaluated the change in the sensory properties of sparkling wines with time (Hood White and Heymann ), consumer and marketing‐related research in the wine science field has tended to focus on table wine, but studies have been published, describing: attitudes of young consumers towards sparkling wine (Charters et al , Thach ); factors influencing consumer preference for sparkling wine, including country of origin and occasion (Schaefer , Charters , Combris et al , Vignes and Gergaud , Culbert et al , Verdonk et al ); consumers' willingness to pay for Champagne (Lange et al ); and the influence of kudos and sentimentality on Champagne purchasing behaviour (Morton et al ). Even those who avoid consuming wine report consumption of sparkling wine during celebrations (McIntyre et al ), ascribing sparkling wine a unique style by context interaction.…”
Section: Introductionmentioning
confidence: 99%
“…All consumer segments were willing to pay more for Champagne than any other style of sparkling wine. This likely reflects the influence of country of origin and price on consumer perceptions of wine quality [64,65]. Evidence also suggests purchasers are willing to spend more per bottle when wine is purchased for special occasions [49].…”
Section: Influence Of Price On Consumer Purchasing Behaviormentioning
confidence: 99%